O projeto natureza & criança: aprendendo com animais e plantas como proposta de ações de educação ambiental na formação de estagiários da área de Biociências e alunos do ensino fundamental - Ribeiro, Gabriela Dávila (2015)
This research describes and analyses the program of projeto natureza & criança: aprendendo com animais e plantas (nature & child project: learning with animals and plants), developed by Universidade de Taubate, aiming contribute to the process of teaching and learning in the sciences fields for children from elementary school and to the formation of biosciences (agronomy, biology and pedagogy) undergraduation trainees that participated on the project. Using an exploratory qualitative nature methodology, interviews were made from the application of questionnaires with the project coordinators, as well as scholars and voluntary trainees that participated on it in 2007 and 2008. The data obtained were treated and discussed from the Bardin s method. The analysis of questionnaires answers enabled a discussion about the perceptions of research individuals, as well as awareness of environmental issues form them. The research demonstrates satisfactory results related to effectiveness of actions and activities developed by project, indicating that the used subjects and strategies contributed to the construction of knowledge on environmental education and entomology on the formation of undergraduation and elementary school students.